The Effect of Climbing Grammar Mountain Game on Students’ Lexicogrammatical Features of Personal Recount Text Mastery (A Study at The Eigth Grade Students of MTS YPKS Padangsidimpuan In 2021/2022 Academic Year) - Dewi Fitriani Sihombing; Asriani Hasibuan; Nina Nurbaidah (Journal MELT (Medium for English Language Teaching), 2022)
The purpose of this research was to found out: 1) The application of Climbing Grammar Mountain Game on Students’ Lexicogrammatical Features of Personal Recount Text Mastery, 2) The Students’ Lexicogrammatical Features of Personal Recount Text Mastery before and after using Climbing Grammar Mountain Game, 3) Whether there is any significant effect of Climbing Grammar Mountain Game on Lexicogrammatical Features of Personal Recount Text Mastery at the Eighth Grade Students of MTs YPKS Padangsidimpuan.This research used experimental method with the pre-experimental designusing one-group pretest posttest design. The population of this research was the VIII grade students consist of 156 students and the samples were 25 students gotten by using purposive sampling. The writer used observation sheet and test as an instrument. The result of this research: 1) The application of climbing grammar mountain game was 3.7, it was categorized “Good”, 2) the mean score pretest of students’ lexicogrammatical features of personal recount text was 53,2 it was categorized “Bad”. Meanwhile after using climbing grammar mountain game was 73,4 it was categorized “Good”. 3) The result of data analysis showed that ttest= 10.6, while the table df score of ttable 5% significant level was 2.06. It means that ttest was higher than ttable(10.6> 2.06). So, the hypothesis is accepted. It means that, there is significant effect of using climbing grammar mountain game on students’ lexicogrammatical features of personal recount text mastery at the eighth grade students of MTs YPKS Padangsidimpuan 2021/2022 Academic year.